Determinan Perasaan SDM (Cognitive Reappraisal dan Expressive Suppression) Terhadap Job Search Behavior (Studi kasus pada mahasiswa tingkat akhir sebuah PTS di Jakarta Pusat) - Hanan Wihasto (Journal Competency of Business, 2020)
This study aims to determine (1) the effect of cognitive reappraisal on job search behavior, (2) the effect of expressive suppression on job search behavior, (3) the effect of anxiety on job search behavior, (4) the role of anxiety as a mediation in the influence of emotional regulation strategies and job search behavior. The population in this study were final year students of a private university in Central Jakarta in 2015. The sample used in this study was 210 people. The sampling technique used proportional sampling method. In this study, the validity test used Confirmatory Factor Analysis (CFA), the reliability test used the Cronbach's Alpha method and hypothesis testing used the causal steps method with SPSS software. The results of this study indicate that cognitive reappraisal has a positive and significant effect on job search behavior, meanwhile expressive suppression has a negative and significant effect on job search behavior, and anxiety partially mediates the effect of emotional regulation strategies on job search behavior.